CETE91 tool condition monitoring using ae signal in turning of ASSAB-705 steel - Choudhury, I.A.; Lee, C.Y.; Bhuiyan, M.S.H.; Nukman, Y. (2010)
The progressive wear of cutting tools and other occurrences involved with chatter vibration often pose limiting factors on the achievable productivity in machining processes. An effective in-process monitoring system for tool condition therefore offers the unique advantage of relaxing the process parameter constraints and optimizing the machining production rate. This paper briefly presents a monitoring technique using acoustic emission (AE) signal in turning. An interpretation method of the AE signal using FFT is explored and attributed the signal to the tool condition .The tool wear; the chipping and the tool breakdown all have their own effect on acoustic emission (AE) signal generated during turning. The AE generated from the sources is investigated based on the energy dissipation principle. Cutting tests were conducted to determine the amplitude relationship between RMS AE and tool condition using FFT. The result shows that in gradual tool wear, the dominating frequency range lies between 20 Hz – 260 Hz for the tool-work-material combination used. It is shown that the FFT is capable to describe the AE signal and it deserves to extract features of the signals. Key words: Acoustic emission, Fourier transform, Tool condition monitoring.